2001
DOI: 10.1063/1.1383014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface processing and passivation on carrier concentrations and transport properties in AlGaN/GaN heterostructures

Abstract: The influence of surface chemical treatments and of deposition of a SiO 2 surface passivation layer on carrier distributions and mobility in Al x Ga 1Ϫx N/GaN heterostructure field-effect-transistor epitaxial layer structures is investigated. Surface chemical treatments are found to exert little influence on carrier distribution and mobility. Deposition of a SiO 2 surface passivation layer is found to induce an increase in electron concentration in the transistor channel and a decrease in mobility. These chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 27 publications
2
29
1
Order By: Relevance
“…It has been demonstrated that silicon nitride can be used as the material for a passivation to reduce the current collapse and microwave power degradation in intentionally undoped AlGaN/GaN HEMTs [2]. Consequently, many controversial results were published on passivated AlGaN/GaN HEMTs [3,4]. On the other hand, it is known from Si-electronics that the properties of passivation layers strongly depend both on the process of deposition and on the type of passivation layer [5].…”
Section: Introductionmentioning
confidence: 97%
“…It has been demonstrated that silicon nitride can be used as the material for a passivation to reduce the current collapse and microwave power degradation in intentionally undoped AlGaN/GaN HEMTs [2]. Consequently, many controversial results were published on passivated AlGaN/GaN HEMTs [3,4]. On the other hand, it is known from Si-electronics that the properties of passivation layers strongly depend both on the process of deposition and on the type of passivation layer [5].…”
Section: Introductionmentioning
confidence: 97%
“…The electrical properties of 2DEG can be closely related to the surface properties of the GaN HFETs via polarization effects [11,12]. On the baisis of a simple electrostatic analysis, it is speculated that a change in the surface potential of GaN HFETs can lead to a change in the 2DEG density [13]. The surface potential distribution of GaN HFETs with selective-area deposition of Si atoms was investigated by Kelvin probe force microscopy (KFM).…”
Section: Methodsmentioning
confidence: 99%
“…Surface properties of AlGaN/GaN heterostructures are closely connected to the 2DEG density via polarization effects [7,8]. Dang et al have speculated, on the basis of a simple electrostatic analysis, that surface passivation on AlGaN/GaN heterostructures can change AlGaN surface potential, thereby leading to a modulation in the 2DEG density [9]. In this study, we directly measure AlGaN surface potentials in AlGaN/GaN heterostructures with and without Cat-CVD SiN passivation using x-ray photoelectron spectroscopy (XPS), and experimentally demonstrate that a reduction in the AlGaN surface potential is actually induced by Cat-CVD SiN passivation, which is likely to be a significant cause of increase in the 2DEG density.…”
mentioning
confidence: 99%